2011
DOI: 10.1016/j.alcr.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Now or later? The Theory of Planned Behavior and timing of fertility intentions

Abstract: This article focuses on the time frame of intentions to have a child. For both parents and childless people we compare those who want a child now with those who intend to have a child within the next three years. Based on the Theory of Planned Behaviour and using data from Norway (N=1,307), we investigate the role of attitudes, subjective norms and perceived behavioural control on these two different time frames in fertility intention. The results show that subjective norms have a significant effect on the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 27 publications
10
118
0
7
Order By: Relevance
“…Previous research on childbearing intention has focused on the influence of attitudes, norms, and the social network or social capital (Schoen et al 1997;Philipov, Spéder, and Billari 2006;Bühler and Fratczak 2007;Ruckdeschel 2007;Bühler 2008;Billari, Philipov, and Tester 2009;Dommermuth et al 2009;Klobas 2010), gender equity (Mills et al 2008;Neyer and Rieck 2009), happiness (Billari 2009), and religion (Hayford and Morgan 2008). Moreover some studies have dealt with the impact of the employment situation on childbearing intentions.…”
Section: Problemmentioning
confidence: 99%
“…Previous research on childbearing intention has focused on the influence of attitudes, norms, and the social network or social capital (Schoen et al 1997;Philipov, Spéder, and Billari 2006;Bühler and Fratczak 2007;Ruckdeschel 2007;Bühler 2008;Billari, Philipov, and Tester 2009;Dommermuth et al 2009;Klobas 2010), gender equity (Mills et al 2008;Neyer and Rieck 2009), happiness (Billari 2009), and religion (Hayford and Morgan 2008). Moreover some studies have dealt with the impact of the employment situation on childbearing intentions.…”
Section: Problemmentioning
confidence: 99%
“…The intention to become a parent (parity zero) marks a crucial transition in life, whereas the intention of a higher parity transition (to second or higher birth order child) is qualitatively different and strongly affected by the experience of parenthood (Dommermuth, Klobas, and Lappegård 2011). Therefore the analysis was stratified by parity, with 4,215 daughters without any children, and 8,391 daughters with at least one child.…”
Section: Samplementioning
confidence: 99%
“…We focus on short-term intentions for both theoretical and practical reasons. Previous studies (Dommermuth et al 2009;Philipov 2009) have shown that short-term intentions are more accurate than long-term ones, due to the fact that people are more capable of predicting their life situation within a shorter period of time. A second more practical reason is that we use a panel dataset in this study that follows individuals for a period of 3.5 years, which permits us to examine their intentions and then behavioural outcomes during this time span.…”
Section: Introductionmentioning
confidence: 99%